One-year dynamic MRI follow-up after vaginal mesh repair: evaluation of clinical, radiological, and quality-of-life results - Brocker, Kerstin A.; Alt, Céline D.; Rzepka, Jakub; Sohn, Christof; Hallscheidt, Peter (Acta radiologica, 2015)
Background Pelvic organ prolapse (POP) is a common disorder in elderly women often surgically repaired with alloplastic meshes; yet knowledge of the pelvic floo...
Gesehen am 28.05.2020